2017
DOI: 10.1155/2017/4890421
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Analysis of Suspended Sediments Concentration Using Mobile and Static Acoustic Doppler Current Profiler Instruments

Abstract: The application of Acoustic Doppler Current Profiler (ADCP) can be used not only for measuring ocean currents, but also for quantifying suspended sediment concentrations (SSC) from acoustic backscatter strength based on sonar principle. Suspended sediment has long been recognized as the largest sources of sea contaminant and must be considered as one of the important parameters in water quality of seawater. This research was to determine SSC from measured acoustic backscattered intensity of static and mobile A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Analysis using ANN required data to be selected with linear forms such as suspended sediment concentration (mg l -1 ) from previous research [1] and abundance of zooplankton (ind m -3 ) which was calculated by the relationship between MVBS and TS values [14]. Using linear forms, the data from the training carried out on logarithmic data (dB) from MVBS and RB obtained a small correlation coefficient (r), around 0.1.…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis using ANN required data to be selected with linear forms such as suspended sediment concentration (mg l -1 ) from previous research [1] and abundance of zooplankton (ind m -3 ) which was calculated by the relationship between MVBS and TS values [14]. Using linear forms, the data from the training carried out on logarithmic data (dB) from MVBS and RB obtained a small correlation coefficient (r), around 0.1.…”
Section: Classificationmentioning
confidence: 99%
“…However, these techniques, in addition to being time-consuming, may result in low accuracy. The other limitation is that the results' linearity level with environmental conditions remains unknown [1]. The accuracy of the processing results also has limitations for prediction in the future.…”
Section: Introductionmentioning
confidence: 99%
“…ADCP instruments have significant advantages in detecting zooplankton because of their wide coverage area of three or four transducers [27]. The consistency of the backscatter value from each transducer was analyzed by using cross-beam calibration [17,20]. Aside from that, the acoustic waves from ADCP instruments still have sound attenuation from the geometrical spreading and sound absorption in the water column.…”
Section: Mean Volume Backscattering Strength (Mvbs) Computationmentioning
confidence: 99%
“…However, from the previous research, although the observation was simultaneous, it was reported that the precision of the backscattered signal measured by ADCP has a limitation in measuring and detecting different types of scatterers, for example, bubbles, zooplankton, and suspended sediments which individually and differentially affect the acoustic backscatter signal [18][19][20]. On the other hand, the use of single frequency acoustic in ADCP, in particular, is hardly able to discriminate the scatterers [21] and difficult to use to observe the zooplankton presence [9,22].…”
Section: Introductionmentioning
confidence: 99%
“…Sinyal akustik ADCP yang berupa intensitas gema dalam satuan count setelah dikonversi ke dalam satuan desibel (dB) digunakan untuk mengidentifikasi tingkat kekeruhan. Satu count setara dengan 0,43 dB pada RD Instruments (Dwinovantyo et al, 2017).…”
Section: Metodologiunclassified